2009
DOI: 10.1111/j.1524-4725.2009.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Rejuvenation with 1,064-nm Q-Switched Nd

Abstract: The QSNYL is a safe and effective rejuvenation modality in Asian patients. Topical carbon solution application did not enhance laser efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 13 publications
1
29
0
1
Order By: Relevance
“…In addition, previous reports suggested that QS Nd:YAG‐induced selective photothermolysis was responsible for collagen breakdown and reduced collagen production in keloids 14,15,20 . QS Nd:YAG‐induced neocollagen (not keloidal collagen) production and collagen remodelling by thermal damage might also have a role in the clinical improvement of keloids and hypertrophic scars 21,22 . Bowes et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous reports suggested that QS Nd:YAG‐induced selective photothermolysis was responsible for collagen breakdown and reduced collagen production in keloids 14,15,20 . QS Nd:YAG‐induced neocollagen (not keloidal collagen) production and collagen remodelling by thermal damage might also have a role in the clinical improvement of keloids and hypertrophic scars 21,22 . Bowes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Various non-ablative laser or light sources, including 585-nm pulsed dye laser, 1064-nm Q-switched or 1320-nm Nd:YAG lasers, 1540-nm erbium:glass fractional laser, intense pulsed light, and radiofrequency devices, have been used for skin rejuvenation with variable clinical outcomes (1)(2)(3). Many reports have demonstrated that 1064-nm Nd:YAG laser treatment increases the homogenization of collagen via the penetration of laser energy-induced thermal damage to the deeper dermis resulting in improvement of skin texture and wrinkles (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Canfield systems are designed to produce consistently positioned beforeand-after images by using chin and forehead rests as well as a guide light. The VISIA system has multiple applications in aesthetic medicine including the evaluation of outcomes following skin rejuvenation with lasers [17,18].…”
Section: Visiamentioning
confidence: 99%